Analysis of Continuous Seismic Profiles - Leenhardt, O. (The International Hydrographic Review, 2015)
The sequence of operations called continuous seismic profiling is as follows. At a given position, aboard a vessel underway, a short elastic pulse is transmitted through the water, then the echo from the bottom and the elastic discontinuities of the subbottom are received and are amplified and filtered. Next these are inscribed on the paper record, and all these processes are then repeated several times per second or per minute. J.B. Hersey has pioneered this method which yields a time section of the substrata, and its use is becoming increasingly widespread. The resolution of a seismic signal depends on the transmitter’s frequency band B and its energy — i.e. its penetration — on the signal length T and on the characteristics of the instrument. In general signals in the form of pulses are used. Relation BT = 1 means that we only obtain a resolution of less than 2% of the penetration. Furthermore, the depth of the emitter and the receiver, as well as the sequence of the substrata reflectors, filter the signal which is moreover partially absorbed by the soil. The characteristics o f the sound sources will therefore be chosen in function of the result desired, that is, either a deep penetration and weak resolution or else the reverse, or again a compromise between the two solutions. Electronic noise from the bottom, noise from the sea, the hydrodynamic noise arising from the movement of the receiver, and the noise of the instrumented boat, all such interference can be reduced. For the geophysicist the most important task is to achieve a good record. It is not simple to put to sea again. Therefore every care has to be taken to see that the work at sea is well done. Back on land and well rested, the analysis of the records is undertaken. The seismic signal reflected by a particular reflector has well marked and individual characteristics that are functions of the geology of the subbottom. An analysis of the character of the reflection makes it possible to distinguish between the various reflectors and to follow them throughout the whole study. Distinguishing between the different types of character and studying the shape of the reflections, we are able to recognize the geologic characteristics of the formations we have encountered. This, in effect, is tectonic analysis. In order to be able to interpret the profiles the velocity of propagation of elastic waves in the subbottom must be known. At sea there are hardly any possibilities for drilling to achieve such measurements. Although we may succeed in measuring the velocity in unconsolidated sediment by various methods, we are generally obliged to use data from refraction measurements for the deeper layers, and these do not always yield valid results by reason of the lateral heterogeneity of the subbottom. Making these refraction measurements at sea is difficult. The interpretation is carried out in various different ways depending on the object of the study.